Virial expansions and augmented van der Waals approach: Application to Lennard-Jones-like Yukawa fluid - Trokhymchuk, A.; Melnyk, R.; Nezbeda, I. (Condensed Matter Physics, 2015)
We argue that recently proposed [Melnyk et al., Fluid Phase Equilibr., 2009, 279, 1] a criterion to split the pair interaction potential into two parts, one of which is forced to be responsible for excluded volume in the system, results in the expressions for virial coefficients that improve the performance of the virial equation of state in general, and at subcritical temperatures, in particular. As an example, application to the Lennard-Jones-like hard-core attractive Yukawa fluid is discussed. Показано, що запропонований недавно [Melnyk et al., Fluid Phase Equilibr., 2009, 279, 1] критерiй розбиття
потенцiалу парної взаємодiї на двi частини, одна з яких описує як можна точнiше виключений об’єм в
системi, приводить до виразiв для вiрiальних коефiцiєнтiв, якi суттєво покращують точнiсть вiрiального
рiвняння стану в цiлому та для температур нижчих за критичну, зокрема. Як приклад, розглянуто застосування до Леннард-Джонсiвської моделi твердих сфер з притяганням Юкави.